The Development of Imitation in Children with Autism Spectrum Disorders and the Developmental Role of Imitation - Meral Çilem ÖKCÜN AKÇAMUŞ; Figen TURAN (Hacettepe University, 2016)
Imitation skills play an important role in child development during early childhood. Children with autism spectrum disorders (ASD) exhibit limitations in their imitation skills and these limitations differentiate autistic children from other children with developmental disorders. Studies revealed that early imitation skills of children with autism spectrum disorders are related to expressive language, receptive language, lexical development, social interaction and play development which show that imitation also plays a vital role in autistic child development. Additively; in all these imitation skills, children with autism spectrum disorders exhibit a rather poor performance compared to their typically developing peers and children diagnosed with different developmental disorders. They have more difficulty in spontaneous imitation behaviours in natural environments than those which take place in structured environments. This shows that even children with autism spectrum disorders acquire imitation skills, they experience difficulties in understanding the social role of imitation and using imitation for social interaction and social learning in natural contexts.